Improving coproovoscopic diagnostics of trichostrongylosis of geese - Starodub , Ye. S. (Scientific Progress & Innovations, 2019)
The purpose of the article is to improve the method of coproovoscopic lifetime diagnostics of geese trichostrongylosis. Methods of research. Commonly known methods of lifetime coproscopic diagnostics (of Fülleborn, Kotelnykova-Khrenova, Mallory, Melnychuka) using flotation solutions were used, and also the methods were improved. The determining of the invasion intensity indices in the process of diagnosing geese trichostrongylosis was carried out. The research results. It has been established that the improved method with the use of combined flotation fluid was proved to be the most effective in diagnosing trichostrongylosis of geese than methods with the use of saturated sugar solution (up to 54.99 %), with a saturated solution of ammonium nitrate (up to 51.30 %), with urea (up to 23,11 %). Moreover, the time taken to study one sample of the litter is 17 minutes. The elements of scientific novelty. The improving and testing of a new flotation method, which has high indicators of diagnostic effectiveness for geese trichostrongylosis have been carried out. Practical significance. The obtained results allow us to recommend the improved method for introduction in production in order to timely and effectively diagnose trichostrongylosis in poultry farming.